Morphological and Compositional Study of Nitrogen-TiO₂ Anchored Composite with Azo Dyes in a DSSC (International Journal of Scientific Research in Science and Technology, 2024)
The efficiency of Dye-Sensitized Solar Cells (DSSCs) heavily relies on the structural and morphological characteristics of the photoanode materials [1]. This study investigates the effects of Nitrogen on TiO2 and the subsequent anchoring with two different Azo dyes RP and VC, to evaluate their impact on DSSC performance [2]. A comprehensive analysis was conducted using Scanning Electron Microscopy (SEM) to study the surface morphology of pure TiO2, Nitrogen TiO2 (N-TiO2), and N-TiO2 composites with RP and VC Azo dyes [3]. Energy-Dispersive X-Ray Spectroscopy (EDS) provided insight into the elemental composition and confirmed the successful incorporation of nitrogen into the TiO2 structure. The SEM images reveal significant morphological differences between the pure and N-TiO2 samples, as well as changes induced by the azo dye anchoring [4]. The Nitrogen incorporation was found to increase surface roughness and enhance dye adsorption [5]. A comparative analysis of the N-TiO2 composite with RP and VC azo dyes highlights variations in dye distribution and surface coverage, which may influence light absorption and charge transfer efficiency. The findings provide valuable insights into the design of optimized photoanode materials, aiming to improve the photovoltaic performance of DSSCs [6].